Encyclopaedia of health nutrition and family welfare - Wal, S; Mishra, Ruchi (New Delhi Sarup and Sons, 2000)
The three volumed encyclopeadia:Food habits are not necessarily related to nutrition and life style pattern. These are related with culture, environment and availability of food. Therefore,life style patterns and food habits must be linked with nutritiona
Contents: v.1. Health and family welfare in developing countries -v.2. Health and nutrition programme for women and child development -v.3. Health and family welfare in Uttar Pradesh
Keywords: Health-Encyclopaedias and dictionaries; Nutrition-Encyclopaedias and dictionaries; Family policy; Public welfare